SNP DETECTION OF GnRHR GENE AND ITS ASSOCIATION WITH LITTER SIZE TRAITS IN GIANT PANDA - B. Tang; X. Huang; C. Han; L. Li; K. Xie; X. Li; C. Bao; Y. Huang; B. Luo; Z. Huang; M. Wei; H. Zhang; et al. (Journal of Animal and Plant Sciences, 2019)
In this study, the GnRHR gene polymorphism of the giant panda was detected, and its effects on litter size were analyzed. Thirty-eight giant pandas that were fed under similar conditions were randomly chosen, and polymorphism in the giant panda GnRHR gene coding region was detected by PCR-SSCP. The association between the GnRHR genotypes and litter size traits was carried out with the GLM procedure using the SAS software. The PCR-SSCP test results showed that the T516121C SNP locus existed in the GnRHR gene exon 1, the C504498T SNP locus existed in exon 2, but no SNP locus was found in exon 3. The T516121C and C504498T loci belong to the non-synonymous mutations. The T516121C substitution led to one amino acid mutation (Cys>Arg), as did the C504498T substitution (Ala>Val). In the group of 38 pandas, there were three genotypes at the T516121C and C504498T loci. The chi-square test showed that the T516121C and C504498T loci fit into the Hardy Weinberg equilibrium in the giant panda population (P>0.05). Furthermore, the correlation analysis results indicated that the different genotypes of the C504498T locus in the panda GnRHR gene had significant effects on the average litter size for second births (P≤0.05). The average litter size for second births of giant pandas with the CC genotype was higher than that the size of the DD genotype (P≤0.05). The first births of the giant pandas with the AA genotype had the maximum average litter size, and there was no significant correlation between the T516121C loci with litter size traits of giant panda. Therefore, these results suggest that the C504498T base mutation in the exon 2 of GnRHR could influence the litter size of giant panda. In other words, GnRHR could influence fertility in giant panda.
Keywords: Giant panda; GnRHR; SNPs; PCR-SSCP; Litter traits